SCLEROCHOROIDAL CALCIFICATION MIMICKING CHOROIDAL OSTEOMA: A CASE REPORT: SCLEROCHOROIDAL CALCIFICATION - Vasović, Dolika; Rašić, Dejan M.; Mitrović, Mirjana (Srpski medicinski časopis Lekarske komore, 2025)
Introduction: Sclerochoroidal calcifications are uncommon, benign ocular findings characterized by the deposition of calcium and phosphate within the sclera and adjacent choroid. These lesions are most frequently discovered incidentally during routine ophthalmologic evaluation, particularly in elderly individuals, and may resemble more serious intraocular pathologies. Case report: We present the case of a 62-year-old male patient referred for evaluation of a subretinal lesion in the peripheral retina of the left eye, initially detected during a routine ophthalmologic examination. The patient was asymptomatic, with no visual complaints. Fundus examination revealed a yellowish, placoid lesion with indistinct borders located suprapapillary, between the superior vascular arcades. B-scan ultrasonography demonstrated high internal reflectivity with posterior acoustic shadowing. Fluorescein angiography revealed a hypofluorescent lesion without leakage or staining. The lesion remained stable over several years, and systemic workup showed no evidence of metabolic abnormalities. Based on clinical and imaging findings (B-scan ultrasonography and fluorescein angiography), the diagnosis of sclerochoroidal calcification was established.Conclusion: Sclerochoroidal calcifications may clinically and ultrasonographically mimic more serious intraocular lesions. B-scan ultrasonography and fluorescein angiography, play a key role in distinguishing these benign findings from other conditions. In asymptomatic patients without signs of progression, annual follow-up is recommended, with no need for therapeutic intervention.
Keywords: sclerochoroidal calcification; choroidal osteoma; fluorescein angiography; calcified intraocular lesions